Pengembangan Video Pembelajaran Materi Voice Over Internet Protocol (VOIP) Kelas XI di SMKN 3 Garut - Hamidah, Siti Arfah; Rahadian, Dian; Bhakti, Demmy Dharma (Universitas Nusantara PGRI Kediri, 2026)
One innovative solution to support the learning process in schools is the use of video-based learning media. This research was conducted with the aim of developing interactive learning videos tailored to students’ needs and aligned with the learning outcomes in schools. The method used was Research and Development with the ADDIE development model. The video product developed using CapCut, Canva, and Lumi was assessed as “highly feasible” by the material expert validator with an average score of 4.38, and by the media expert validator with an average score of 4.81. The product trial conducted with students obtained an average score of 4.59, categorized as having “Very High Acceptance.”. The results of the evaluation of the developed video-based learning media indicate that the product is highly suitable for use in classroom learning activities, as it helps make the learning process more effective, engaging, and easier for students to understand.